Project management: the managerial process - Gray, Clifford F (McGraw Hill education (I) Pvt. Ltd, 2014)
Project management: the managerial process / Gray, Clifford F. -- New Delhi: McGraw Hill education (I) Pvt. Ltd., 2014 658.404 G778 6th ed No. of Copies : 1